2022
DOI: 10.3390/coatings12050677
|View full text |Cite
|
Sign up to set email alerts
|

Defective ZnO Nanoflowers Decorated by Ultra-Fine Pd Clusters for Low-Concentration CH4 Sensing: Controllable Preparation and Sensing Mechanism Analysis

Abstract: To detect low concentration of CH4 is indeed meaningful in industrial manufacturing, such as the petrochemical industry and natural gas catalysis, but it is not easy to detect low concentration of CH4 due to its high symmetrical and stable structure. In this work, defect-rich ZnO1−x nanoflowers (NFs) were synthesized by a two-step route so as to obtain defect-enhanced gas-sensing performance, namely hydrothermal synthesis followed by H2 treatment. In order to achieve low-concentration detection of CH4, the ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The nanocomposite films showed excellent mechanical and antibacterial properties displaying polymer-based nanocomposite antibacterial coating which could be applied in several fields, such as textile, leather, packaging, paper making and indoor wall coating. Chen et al 113 fabricated ZnO nanoflowers and also metal decorated nanoflowers which showed excellent sensing applications. Tang et al 114 produced ZnO NRs, nanowalls and nanoflowers via a hydrothermal route.…”
Section: Spherical 3d Zno Nanostructure Based Thin Filmsmentioning
confidence: 99%
“…The nanocomposite films showed excellent mechanical and antibacterial properties displaying polymer-based nanocomposite antibacterial coating which could be applied in several fields, such as textile, leather, packaging, paper making and indoor wall coating. Chen et al 113 fabricated ZnO nanoflowers and also metal decorated nanoflowers which showed excellent sensing applications. Tang et al 114 produced ZnO NRs, nanowalls and nanoflowers via a hydrothermal route.…”
Section: Spherical 3d Zno Nanostructure Based Thin Filmsmentioning
confidence: 99%
“…Therefore, in order to increase the selectivity to CH 4 and reduce the cross-sensitivity to other interfering gases, the reasonable functional modification of CNTs is a promising strategy [17][18][19]. Studies have shown that nanocomposites provide high-performance gas detection [20]: VO 2 can be sensitive to CH 4 [21,22], and noble Pd has a favorable catalytic effect on CH 4 [23][24][25]. In addition, due to the transconductance of field-effect transistor (FET) sensors, the gas sensors based on the FET structure have a strong amplification effect of weak signals and can realize the detection of lower concentrations of gas molecules with high sensitivity [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this progress, it is still a challenge to develop novel CH 4 sensors to meet the growing demands (e.g., lower operating temperatures and faster response/recovery rates). Since the principle of CH 4 sensing is the catalytic oxidation of CH 4 , which is promoted by Pd, it is facile to consider the structural modification of Pd to further improve the CH 4 sensing performance [27]. In recent years, researchers have proposed an important strategy: the introduction of a second metal component as a promoter to enhance the catalytic oxidation of CH 4 at reasonably low temperatures by increasing the activity of the catalyst, which significantly improves the gas sensing performance [28][29][30].…”
Section: Introductionmentioning
confidence: 99%